Abdominal Tumor in a 14-Year-Old Adolescent: Imperforate Hymen, Resulting in Hematocolpos-A Case Report and Review of the Literature - George Marios Makris; Doris Macchiella; Dennis Vaidakis; Charalampos Chrelias; Marco Johannes Battista; Charalampos Siristatidis (Hindawi Limited, 2015)
Background. Abdominal masses in female adolescents are uncommon. A rare cause of this condition is hematocolpos due to imperforate hymen. Case. We present a case of an unusually massive asymptomatic abdominal bulk in a 14-year-old female patient, who sought for medical advice after unusual abdominal pain lasting for few weeks. The patient was otherwise asymptomatic, apart from an unusual dramatic expansion of her abdominal wall during the last month. We describe the surgical management and the follow-up of the patient. Summary and Conclusion. Clinicians should keep in mind that an imperforate hymen can cause abdominal growth due to hematocolpos and include it in the differential diagnosis of such a clinical entity in female adolescents. 2D ultrasound is usually efficient for the confirmation of the diagnosis of hematocolpos, but 3D ultrasound is more accurate. Wide excision should be undertaken, as an initial approach, to avoid recurrence.